Reaksi Abnormal Return Dan Trading Volume Activity Sebelum dan Sesudah Ramadhan Effect - Nina Atrina Kudusia; Nilawaty Yusuf; Muliyani Mahmud (Jambura Accounting Review, 2020)
This Research aims to find out the difference between the average of abnormal return and trading volume activity of the transportation companies’ stocks listed in Indonesia Stock Exchange, a period 2014-2018 before and after Ramadhan. The research method is a quantitative method. Th kind of data used is secondary data. The sample is 11 transportation companies listed ini Indonesia Stock Exchange during the period of 2014-2018, while the sampling technique applies purposive sampling. The findings show that there is no difference on the average of abnormal return before and after Ramdahan, and there is no difference on the average of trading volume activity in 2015 and 2018, whereas in 2014, 2016, and 2017 there is a difference on the average of trading volume activity. Meanwhile, the abnormal return and trading volume activity simultaneously influence toward Ramadhan effect with the result of the coefficient determination of 50%, it means that 50% of Ramadhan effect variable is explained by return and trading volume activity.